Assessing Efficacy and Safety: Oxytocin Monotherapy vs. Oxytocin + Carbetocin Combination Therapy - Mohammad Kaif A. Mansuri; Vishwa J. Mehta (International Journal of Tropical Medicines, 2024)
Objective: Comparing the Effectiveness between Oxytocin monotherapy and Oxytocin + Carbetocin. Methods: A prospective, non-randomized, observational study focusing on 221 women with CS was conducted. The patients eligible based on inclusion and exclusion criteria were screened and final sample size was 139. Individual patient data including patient demographics, medical history, OT notes, pre and post CBC reports, and safety data were obtained from the patient records. The study compared between Oxytocin monotherapy which included 67 patients and Oxytocin + carbetocin combination which has 72 pateints. The desired outcome was to compare blood loss, Hb, HCT and the administration of the treatment in preexisting conditions. Results: The incidence of blood loss was higher in Oxytocin monotherapy compared to oxytocin + carbetocin (421.94 ± 120.48 vs 356.25 ± 116.89; P=0.0003) suggesting that addition of carbetocin reduces blood loss and reduces the risk of PPH. The decline in Hb (P=0.16) and HCT (P=0.27) levels between the treatment groups did not show any discernible differences. The Administration of Oxytocin + carbetocin was slightly higher in PIH patients (53.48%) compared to Oxytocin monotherapy (34.88%), however there was no significant difference determined (P=). Also there was no difference in the usage of this treatment groups in Anaemic patients. Conclusion: There was a significant reduction in blood loss when carbetocin was added in the treatment regimen. However it has no effect on the Hb and HCT levels and its increase in utilization in pre-exsiting conditions suggesting no significant difference.
Keywords: Blood loss; CS; HB; PPH; carbetocin; oxytocin